Perbandingan Efektivitas Tablet Hisap Amylmetacresol-dibenal dengan Profilaksis Deksametason Intravena Sebelum Pemasangan Pipa Endotrakeal untuk Mengurangi Kekerapan Nyeri Tenggorok Pascaoperasi: Eddy Harijanto, Riyadh Firdaus, Dedy Kurnia - Journal Manager MACC (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2016)
Post-operative sore throat (POST) is one of the complications that often arise in the general anesthesia with intubation techniques. The purpose of this study was to compare the effectiveness of amylmetacresol-dibenal lozenges with prophylactic intravenous dexamethasone before intubation to reduce the incidence of POST. After approval from Ethics Committee Faculty of Medicine Universitas Indonesia, Ciptomangunkusumo Hospital and consent from patients,a prospective randomized clinical,double-blind trial was done in 121 patients that would undergo surgery under general anesthesia using endotracheal tube. Patients were divided into two groups randomly; Group A 61 people and group B 60 people. Before induction, patients in group A was given amylmetacresol - dibenal lozenges and injection of 2 mL of 0.9% NaCl, while group B was given intravenous dexamethasone 10 mg and placebo lozenges. POST was evaluated by the numerical rating scale (NRS) 3 times, after surgery when Alderette score of 10, 2 hours postoperatively and 24 hours postoperatively. The frequency and degree of POST were recorded and analyzed with Chi-Square test. There were no significant difference in the incidence of POST in both groups after surgery when Alderette score of 10 , h 2, and the 24th hour postoperatively. The degree of POST was not significantly different between the two groups. Amylmetacresol - dibenal lozenges before intubation tube has the same effectiveness of prophylactic intravenous dexamethasone in reducing the incidence of POST.